2013
DOI: 10.1016/s1995-7645(13)60156-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of halophilic Bacillus sp. BS3 able to produce pharmacologically important biosurfactants

Abstract: Based on the findings, the present study concluded that, there is a possibility to develop eco-friendly antimicrobial and anticancer drugs from the extremophilic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 36 publications
0
40
0
1
Order By: Relevance
“…Higher activity was observed against A. niger and A. flavus , less activity was against P. ultimum , F. solani and R. bataticola , no effect was observed on F. oxysporium . Donio et al [43] reported that Bacillus sp. BS3’s biosurfactants possess an important antifungal activity against different pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Higher activity was observed against A. niger and A. flavus , less activity was against P. ultimum , F. solani and R. bataticola , no effect was observed on F. oxysporium . Donio et al [43] reported that Bacillus sp. BS3’s biosurfactants possess an important antifungal activity against different pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…‘Biosurfactants are amphipathic surface active molecules consists of hydrophilic and hydrophobic moieties that act by emulsifying hydrocarbons, increasing their solubilization, and subsequently rendering them available for microbial degradation’ (Donio et al, 2013). There are various classes of biosurfactants, among which the major classes are phospholipids, glycolipids, lipopolysaccharides, lipoproteins-lipopeptides, fatty acids, neutral lipids, flavolipids, the complete cell-surface itself, as well as those that are not fully characterized (Bodour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A halophilic Bacillus sp. BS3 produced biosurfactant that conferred anticancer effect on the mammary epithelial carcinoma cell (Donio et al 2013). It heralded that extreme habitats can be sampled for novel lipopeptides.…”
Section: Bioprospecting Of New Lipopeptidesmentioning
confidence: 99%